Foreign accents Chinese American verse from exclusion to postethnicity - Yao, Steven G., 1965- (New York ; Oxford : Oxford University Press, 2011)
This book undertakes linguistically informed analyses to examine the various transpacific signifying strategies by which different poets of Chinese descent in the United States have sought to employ or represent elements of a particular cultural tradition in their articulations of an ethnic subjectivity, including writings entirely in Chinese.
Description based on print version record.
Also issued in print format.
Includes bibliographical references and index.
Keywords: American poetry -- Chinese authors -- History and criticism; American poetry -- 20th century -- History and criticism; Chinese Americans in literature